Holocene evolution of the buried tidal sand body in the North Jiangsu Plain of China revealed by luminescence dating - Nian, Xiaomei; Zhang, Weiguo; Wang, Xuemei; Qiu, Fengyue (Frontiers in Marine Science, 2024)
In the northern Jiangsu coastal zone of China, the buried tidal sand body (BTSB) is suggested to share a similar origin with the offshore radial sand ridge system in the southwestern Yellow Sea. However, its chronological framework remains inadequately understood. This study conducted optically stimulated luminescence (OSL) dating of both silt-sized and sand-sized quartz on core LDC from the southwestern end of the BTSB. Together with data from the previously studied core XYK closer to the current coastline, this study aims to clarify the chronology of the BTSB and refine its evolution history. The results indicate that in both cores, sand-sized quartz provides more reliable age estimates than silt-sized quartz for the sandy sediment layers. Additionally, the discrepancy between ages derived from the single-grain central age model and the minimum age model is smaller within the top 11 m of sediment, which was deposited over the last 0.9 ka. This period corresponds well with the southern migration of the Yellow River and its sediment discharge into the Yellow Sea from 1128 to1855 CE, suggesting that distinct sediment sources from the Yellow and Yangtze Rivers may account for the observed differences in OSL characteristics. The OSL ages reveal significant temporal variations in sedimentation rates during the Holocene, with the most rapid deposition occurring between 1.2–0.4 ka and 10–8 ka in core LDC, and between 2–1 ka in core XYK. Together with dating results from the central part of the BTSB, it reveals complex spatiotemporal variations in sediment accumulation and emphasizes the need for detailed sediment sampling and dating to fully elucidate the evolutionary history of the coastal plain.